Monster birthday party - Freedman, Sally; Hearn, Diane Dawson (Niles, Ill. : Whitman, 1983)
With deft waves of the hand, a rich boy$1 (Bs kindly butler enlivens Peter$1 (Bs birthday celebration with sedate uncles and aunts by producing messy, but merry monsters.s
Keywords: Birthdays -- Fiction; Monsters -- Fiction